Pengaruh Ukuran Perusahaan dan Kepemilikan Manajerial terhadap Penghindaran Pajak dengan Transaksi Hubungan Istimewa Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2010-2018) - Kaca Dian Meila (LPPM Universitas Informatika dan Bisnis Indonesia, 2020)
This objective of this research is to examine empirically the infuence of firm size and managerial ownership of tax avoidance through related party transaction as intervening variable. The Object of this research is firm size, managerial ownership, tax avoidance and related party transaction. Population of this research is mining companies which are registered in Indonesia Stock Exchange (BEI) Period 2010-2018. The sample of the population consist of 322mining companies. Data technique analysis used in this research is panel data regression with sobel test. Based on statistical test and hypothesis test in the level of significance α = 0,05 can be proved that in partially firm size and managerial ownership has a positive significant effect of related party transaction, related party transaction has a positive significant effect of tax avoidance, firm size has a negative effect significant, managerial ownership has a negative effect and not significant effect of tax avoidance, related party transcation can be moderate leverage and managerial ownership of tax avoidance.